2021
DOI: 10.1002/jso.26739
|View full text |Cite
|
Sign up to set email alerts
|

Quilting following mastectomy reduces seroma, associated complications and health care consumption without impairing patient comfort

Abstract: Background An important complication following mastectomy is seroma formation. Quilting, in which skin flaps are sutured to the underlying muscle, is reported to reduce seroma incidence, but might induce pain and impair shoulder function. Main objective is to compare quilting with conventional wound closure, regarding seroma incidence, health care consumption, and patient discomfort. Methods In a combined prospective and retrospective study, 254 patients undergoing mastectomy and/or axillary lymph node dissect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 33 publications
(99 reference statements)
0
23
0
Order By: Relevance
“…5 The SAM-trial showed that shoulder mobility seems to be equally affected in patients undergoing mastectomy with or without flap fixation using sutures. 10,15,16 There was a gradual decrease in shoulder mobility disability scores in all groups after mastectomy, suggesting that shoulder mobility in general worsens after mastectomy. Cosmesis and especially skin dimpling do not seem to differ between groups.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…5 The SAM-trial showed that shoulder mobility seems to be equally affected in patients undergoing mastectomy with or without flap fixation using sutures. 10,15,16 There was a gradual decrease in shoulder mobility disability scores in all groups after mastectomy, suggesting that shoulder mobility in general worsens after mastectomy. Cosmesis and especially skin dimpling do not seem to differ between groups.…”
Section: Discussionmentioning
confidence: 96%
“…Methods vary in technique (running or interrupted), suture size (Vicryl 0 to 3-0), distance between sutures (2-5 cm), and location. 2,3,6,8,10,[12][13][14][15] The results of this article should be used to provide a clear guideline on how to perform flap fixation when using sutures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We additionally evaluated the incidence of hematoma after breast cancer surgery. We discovered 11 studies that evaluated hematoma (Eichler et al, 2016; Huang et al, 2021; Khater et al, 2015; Mazouni et al, 2015; Myint et al, 2020; Ohlinger et al, 2018; Ouldamer et al, 2015; van Bastelaar et al, 2016; van Zeelst et al, 2022; Vettuparambil & Subramanya, 2021; Wu et al, 2020) as an outcome when comparing flap fixation and drain placement techniques in breast cancer patients undergoing mastectomy representing a population of 1,735 (SG = 798 patients [46%]; CG = 937 patients [54%]). The results of the meta-analysis were not statistically significant but did show a reduction in the rate of hematoma formation in the SG compared with the CG (OR = 0.78; 95% CI [0.6, 1.03]; p = .08).…”
Section: Resultsmentioning
confidence: 99%
“…We reviewed a total of 3,176 articles, screened a total of 304 studies, and analyzed a total of 19 studies that met our inclusion criteria. The studies were conducted between 2010 and 2022, one of which we imported only a few days before conducting our analysis (van Zeelst et al, 2022).…”
Section: Resultsmentioning
confidence: 99%